PENERAPAN PEMBELAJARAN QUANTUM TEACHING UNTUK MENINGKATKAN MOTIVASI DAN PRESTASI BELAJAR IPA PADA MATERI SISTEM PERNAFASAN - Dewi Santi (Jurnal Dedikasi Pendidikan, 2020)
Quantum Learning Model in class VIII.C SMP Negeri 1 Jaya, Aceh Jaya Regency in learning science of respiratory system material. This type of research is a classroom action research with a descriptive method that uses two cycles, each cycle consisting of stages including: planning, action, observation, and reflection. The subjects in this study were science teachers and students of class VIII.C, SMP Negeri 1 Jaya, Aceh Jaya Regency, Academic Year 2019/2020. The instruments used in this study were observation sheets and test sheets. Observation sheets are used to study the activities of teachers and students, while the test sheets are used to determine the learning outcomes of science students. The results showed that student learning outcomes improved where in the first cycle classical students had only reached 70% increase to 90% at the end of the second cycle. This shows that this research was successful because the students' completeness had reached an indicator of success over 85% of students had been thoroughly approved. Using the Quantum Teaching-learning model is able to provide opportunities for students to actively discuss in groups and motivate students in learning, so that student learning achievement increases. From the results of this data analysis, it can be concluded that the application of the Quantum Teaching learning model can improve the learning outcomes of science students in class VIII.C of SMP Negeri 1 Jaya.